First records of invasive snail Melanoides tuberculatus (Gastropoda: Prosobranchia: Thiaridae) to the Iguazú River basin, Argentina – Brazil - Gutierrez Gregoric, Diego E. (2007)
In this work is reported the first record of Melanoides tuberculatus in the Iguazú River basin (Argentina-Brazil). This species is native to southern Asia and was anthropogenically introduced to America in the 1960s decade. Sixteen specimens (one adult and 15 juvenile) of M. tuberculatus were recorded at only one site, the rapids of Iguazú River at Isla San Martín, Iguazú National Park, Argentina, in June 2005. This finding of M. tuberculatus specimens suggests the presence of a stable population that would represent a threat to the native mollusk fauna, given that this species promotes replacement and impoverishment of mollusk diversity.